Research about Three Dimensional Reconstruction of Medical Image - Linan Fan; Xin Wang; Guangyuan Zhang; Qiechun Chen (Institute of Advanced Engineering and Science, 2013)
In this paper, through comparison of different reconstruction algorithms for volume rendering, we put forward Ray Casting algorithm as the scheme of 3D reconstruction of medical image. We improved the image synthesis operator, and combined section sampling mode to reconstruct the image. Finally we rendered images on GPU. By using improved operator, we not only made the rendering speed accelerated, but also made the quality of rendering images improved. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2084